Modeling and Optimization of Structural Parameters for High-Efficiency Multi-Jet Polishing of Optical Glass - Zhongchen Cao; Yiwei Miao; Ming Wang; Zhenfeng Zhu (Micromachines)
Multi-jet polishing (MJP) is a promising method for enhanced polishing efficiency by integrating multiple nozzles, allowing for the high-efficiency polishing of large-scale surfaces. However, the optimization of the structural parameters, such as the distribution form of the nozzles and outlet diameter, remains a critical challenge for achieving uniform and stable polishing performance. This paper presents a dynamic model of MJP based on the theory of fluid dynamic pressure and particle erosion. The flow field and particle motion characteristics in multi-nozzle jet polishing were studied using simulation experiments. The influence of the nozzle spacing and form and outlet diameter on the flow field characteristics and material removal profile was explored, and the structural parameters of the multi-nozzle polishing tool were optimized. According to the simulation results, two kinds of multi-nozzle polishing tools with a linear arrangement and cross arrangement were processed, and a series of single-point and surface polishing experiments was carried out. The optimized multi-nozzle jet polishing tool has no interference in the removal contour of each point, exhibits high consistency and stability, and is consistent with the theoretical model prediction results, which effectively improve the surface polishing efficiency. The results can provide a theoretical and experimental reference for MJP in the ultra-precision and high-efficiency polishing of large-sized components.